Needs Assesment Buklet Edukatif Tematik Integratif untuk Memberikan Pendidikan Kesehatan Reproduksi bagi Peserta Didik Kelas Atas di Sekolah Dasar - Sunarni Sunarni; Raden Bambang Sumarsono; Desi Eri Kusumaningrum; Dedi Prestiadi (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: The research objectives are: 1) conducting a needs assessment and 2) designing the development of an integrative thematic educational booklet and guidelines for its use. The research uses a descriptive quantitative approach. The research was conducted at "SD Laboratorium UM" Blitar City. The sample is 54 respondents in upper-grade elementary school. Meanwhile, to collect data with a questionnaire via a google form. The results of the study: (1) Needs analysis consisting of the background of the students who were most studied was class V, the education of parents of students was on average already S1 and then SMA/SMK/MA. Parents' income is more than IDR 5 million, then IDR 2 million - IDR 4.9 million. Parent's job is another answer, then private employees and entrepreneurs. The physical condition of all children is normal. (2) The design of the educational booklet is that many respondents agree, the size is medium, the thickness is medium (50 sheets), the booklet section consists of the beginning, content, closing, the Beginning of the Educational Booklet consists of the introduction, table of contents, list of pictures. The contents of the booklet consist of clean and healthy behavior, nutrition education, puberty, reproduction, and sexual violence. The closing part of the booklet consists of closing remarks, bibliography, glossary, and contact numbers. Physical appearance is bright and soft (soft). Contents and Materials in the Booklet consist of pictures and text (you can also add diagrams and tables). The color of the contents of the educational booklet is soft.Keywords: Educational booklets; integrative thematics; and reproductive health education Abstrak: Tujuan penelitian yaitu: 1) melakukan analisis kebutuhan (needs assessment) dan 2) merancang pengembangan buklet edukatif tematik integratif dan pedoman penggunaaanya. Penelitian menggunakan pendekatan kuantitatif jenis descriptive. Penelitian dilakukan di SD Lab UM Kota Blitar. Sampel sebanyak 54 responden di SD kelas atas. Sedangkan untuk mengumpulkan data dengan angket via google form. Hasil penelitian: (1) Analisis kebutuhan yang terdiri dari latar belakang siswa yang paling banyak diteliti adalah kelas V, pendidikan orangtua siswa adalah rata-rata sudah S1 selanjutnya pendidikan SMA/SMK/MA. Pendapatan orangtua lebih dari Rp 5 juta selanjutnya Rp 2 Juta – Rp 4,9 juta. Pekerjaan orangtua yaitu jawaban lainnya, selanjutnya pegawai swasta dan wirausaha. Keadaan fisik semua anak adalah normal. (2) Rancangan Buklet edukatif yaitu bahwasannya responden banyak yang setuju, ukuran sedang, ketebalan sedang (50 lembar), bagian buklet terdiri dari awal, isi, penutup, bagian Awal Buklet Edukatif terdiri dari Kata pengantar, daftar isi, daftar gambar. Isi dari Buklet terdiri dari perilaku hidup bersih dan sehat, pendidikan gizi, pubertas, reproduksi, dan kekerasan seksual. Bagian penutup buklet terdiri dari kata penutup, daftar pustaka, glosarium, dan nomor kontak. Tampilan fisik yaitu terang dan soft (lembut). Isi dan Materi dalam Buklet terdiri dari gambar dan tulisan (bisa juga ditambah diagram dan tabel). Warna dari isi Buklet edukatif adalah soft.Kata kunci: Buklet edukatif; tematik integratif; dan pendidikan kesehatan reproduksi